Allez Hop, a nationwide programme for the promotion of physical activity in Switzerland: what is the evidence for a population impact after one decade of implementation?. Issue 15 (11th June 2010) - Wanner, Miriam; Martin-Diener, Eva; Bauer, Georg F; Stamm, Hanspeter; Martin, Brian W
Abstract : Objectives: To present evidence for a population impact of a national physical activity promotion programme after a decade of implementation. Methods: The programme Allez Hop offered local physical activity courses (mainly walking and Nordic walking) once a week over 12 weeks. Data from a pretest posttest survey in 2005 course participants (N=2157 at baseline (of 4130, 52.2%), 1587 at first follow-up (73.6%); smaller subsample with second follow-up) and from repeated cross-sectional national surveys have been analysed regarding changes in physical activity behaviour. Results: The total number of Allez Hop courses was 18 684 between 1997 and 2008. 89.2% of participants were women, the mean age was 48.5 years. The proportion meeting the physical activity recommendations was 31.7% at baseline, in participants with first follow-up data it increased from 33.1% to 42.3% (p<0.001). On the population level in the main user group of Allez Hop (middle-aged women) the proportion not engaging in any sport decreased from 50.1% (1997) to 47.2% (2002) and to 43.1% (2007) (p<0.01). Walking/hiking was the second most frequently performed sport (33.7%) in 2007, with the most remarkable increase since 2000 (+11.1%). Conclusions: Allez Hop was successfully implemented for more than a decade, reached middle-aged women and a high proportion of insufficiently active individuals. Changes in participants' physical activity behaviour must be interpreted cautiously because of low response rates and short follow-up. However, indications for behavioural changes were observed at the population level, even though these data do not allow a causal link to Allez Hop.